Implementation of a bright frequency correlated photon pairs source based on a PPKTP crystal (2021)
The implementation of a bright frequency correlated photon pairs source based on a PPKTP requires two principal parts: the process of Spontaneous Parametric Down-Conversion SPDC taking into account the quasi-phase-matching conditions and a single-frequency-mode laser source with a Gaussian profile. In this project, a theoretical approach of the SPDC process and the conditions needed to have an intense source of correlated photon pairs source are studied; especially, the process dependence of the temperature of the crystal and the pump wavelength. A single-frequency-mode pump laser source is implemented and focused to a PPKTP crystal. The photon pairs source is characterized spatially, in intensity and frequency. Through this, a bright photon pairs source with a coincidence rate per mW of pump power of 199 +- 1 kHz/mW is obtained, which is at least three times bigger than the rate of coincidences of the SPDC process using a traditional nonlinear crystal as a BBO.